Correction: Self-assembled natLiCl–CeCl3 directionally solidified eutectics for thermal neutron detection. Issue 22 (27th May 2020) - Cheng, Shuangliang; Hunneke, Rachel E.; Tian, Mengkun; Lukosi, Eric; Zhuravleva, Mariya; Melcher, Charles L.; Wu, Yuntao
Abstract : Correction for 'Self-assembled nat LiCl–CeCl3 directionally solidified eutectics for thermal neutron detection' by Shuangliang Cheng et al., CrystEngComm, 2020, DOI: ; 10.1039/c9ce01884k .